1983
DOI: 10.1161/01.res.52.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of biphasic contractions in strontium-treated ventricular muscle.

Abstract: SUMMARY. Biphasic contractions were produced in dog trabeculae by replacing 90-95% of the calcium in the bathing solution with strontium. These conditions produced prolonged action potentials accompanied by contractions with two distinct phasic components. The early component disappeared slowly when the remaining Ca ++ was removed, whereas the late component was eliminated quickly when Sr ++ was removed. Manganese ion (0.25 ITIM) preferentially decreased the late component without changing the action potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
(68 reference statements)
5
23
0
Order By: Relevance
“…The release mechanism described in this paper may be identical to the first component of biphasic contractions in multicellular preparations (Braveny & Sumbera, 1972;King & Bose, 1983;Reiter et al 1984;Honore et al 1987a, b;Vierling, 1988). The release component of biphasic contractions was also shown to be sensitive to ryanodine but not blocked by agents which inhibit L-type Ca2+ channels (King & Bose, 1983;Reiter et al 1984;Honore et al 1987 b;Vierling, 1988 existence of a ryanodine-sensitive Ca2+-release mechanism that operated independently of L-current. Interestingly, in these experiments the component of contraction which was inhibited by L-channel blockers was not inhibited by ryanodine (King & Bose, 1983;Vierling, 1988) as also reported in the present study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The release mechanism described in this paper may be identical to the first component of biphasic contractions in multicellular preparations (Braveny & Sumbera, 1972;King & Bose, 1983;Reiter et al 1984;Honore et al 1987a, b;Vierling, 1988). The release component of biphasic contractions was also shown to be sensitive to ryanodine but not blocked by agents which inhibit L-type Ca2+ channels (King & Bose, 1983;Reiter et al 1984;Honore et al 1987 b;Vierling, 1988 existence of a ryanodine-sensitive Ca2+-release mechanism that operated independently of L-current. Interestingly, in these experiments the component of contraction which was inhibited by L-channel blockers was not inhibited by ryanodine (King & Bose, 1983;Vierling, 1988) as also reported in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…The release component of biphasic contractions was also shown to be sensitive to ryanodine but not blocked by agents which inhibit L-type Ca2+ channels (King & Bose, 1983;Reiter et al 1984;Honore et al 1987 b;Vierling, 1988 existence of a ryanodine-sensitive Ca2+-release mechanism that operated independently of L-current. Interestingly, in these experiments the component of contraction which was inhibited by L-channel blockers was not inhibited by ryanodine (King & Bose, 1983;Vierling, 1988) as also reported in the present study. Clearly other studies have found that contractions elicited from a holding potential of -40 mV are sensitive to ryanodine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence it is reasonable to hypothesize that the inotropic response may also be produced by the inhibition of Na', K+-ATPase and subsequent effect on Na'-Ca2+ exchange and elevation of intracellular Ca2". In support of our hypothesis, the studies on biphasic contraction have indicated that the extract primarily increases the delayed slow component (P2), which is caused by divalent cation entry across sarcolemma (King & Bose, 1983). The extract also increased the amplitude of the early component (although to a smaller extent than P2).…”
Section: Discussionsupporting
confidence: 81%
“…Biphasic contraction Biphasic contraction in canine trabeculae was produced as described by King & Bose (1983). Trabeculae were equilibrated in KH solution by stimulating at 0.5 Hz for 1 hour.…”
Section: Methods Isolation Ofdigitalis-like Substance (Dls)-containinmentioning
confidence: 99%